2019
DOI: 10.1111/bcp.13994
|View full text |Cite
|
Sign up to set email alerts
|

Escitalopram population pharmacokinetics in people living with human immunodeficiency virus and in the psychiatric population: Drug–drug interactions and probability of target attainment

Abstract: Aims The aims of this study were to characterize escitalopram pharmacokinetic profile, to identify factors influencing drug exposure, notably drug–drug interactions with antiretrovirals, and to simulate expected exposure under standard dosage regimen. Methods A population pharmacokinetic analysis was performed using NONMEM. A total of 159 plasma concentration measurements were obtained from 39 human immunodeficiency virus (HIV)‐infected and 71 uninfected psychiatric patients. The influence of age, weight, sex,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 55 publications
1
12
1
Order By: Relevance
“…In this study, we created a PopPK model for oral administration of escitalopram in Chinese psychiatric patients, while considering demographic, genetic and physiological indicators. The model-predicted covariates of this analysis were in line with several published studies that describe the population pharmacokinetics of escitalopram (Jin et al, 2010;Akil et al, 2016;Courlet et al, 2019). We showed that CL/F of escitalopram varied nearly sevenfold, ranging from 6.26 to 38.93 L/h, which means that the pharmacokinetics of escitalopram in different populations show large interindividual variations.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In this study, we created a PopPK model for oral administration of escitalopram in Chinese psychiatric patients, while considering demographic, genetic and physiological indicators. The model-predicted covariates of this analysis were in line with several published studies that describe the population pharmacokinetics of escitalopram (Jin et al, 2010;Akil et al, 2016;Courlet et al, 2019). We showed that CL/F of escitalopram varied nearly sevenfold, ranging from 6.26 to 38.93 L/h, which means that the pharmacokinetics of escitalopram in different populations show large interindividual variations.…”
Section: Discussionsupporting
confidence: 86%
“…We showed that CL/F of escitalopram varied nearly sevenfold, ranging from 6.26 to 38.93 L/h, which means that the pharmacokinetics of escitalopram in different populations show large interindividual variations. Some intensive sampling designs with escitalopram CL/F of 20-40 L/h, mostly in healthy Frontiers in Pharmacology frontiersin.org individuals (Søgaard et al, 2005;Nilausen et al, 2011;Chung et al, 2017), and published PopPK models have a CL/F > 20 or even 30 L/h (van Gorp et al, 2012;Courlet et al, 2019;Kim et al, 2021), while our study showed <20 L/h, which may have been caused by sparse data sampling. Similar to the previous PopPK studies, our analysis revealed that age and CYP2C19 phenotype contributed differentially to the variability in the pharmacokinetics of escitalopram.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…To date, several PPK studies on SCIT have been conducted to identify the covariates that may significantly affect the PK characteristics. [16][17][18][19][20][21][22][23] For instance, the influence of CYP2C19 polymorphism on SCIT exposure was found to be substantial. Consequently, diverse dosage regimens were simulated to enable personalized dosing recommendations for distinct populations.…”
Section: Introductionmentioning
confidence: 99%